PEMODELAN DINAMIKA ARUS PERAIRAN INDONESIA YANG DISEBABKAN OLEH ANGIN - Ika Kusumawati (Universitas Teuku Umar, 2016)
Research on current dynamics modelling in Indonesian waters with wind employed as independent variable has been observed. The purpose of this study was to model the hydrodynamic equations due to the influence of the wind in Indonesia waters in the form of visualization described consisting of wind circulation pattern and pattern of current movement in the west and east monsoon season. To analyze the data obtained during the study, researchers used a descriptive approach. The results showed that the west wind season (December, January, and February) blow from the northeast to the southwest then turning southeast. Whereas the east wind season (June, July, and August) blows from the southeast to the northwest and then turn to the northeast. On the surface layer shows the current movement in general follows the movement of the wind direction in which the current speed is very dominant occurred in some waters, such as the Karimata Strait, the Java Sea, the South China Sea, and the Arafuru Sea. The dominant current velocity in the layer of 100-200 m in the water of eastern equator and the South China Sea in the west season has recorded a current speed reaches 20 cm / s. while in the east monsoon which occurs in the equatorial waters of the eastern part, in the Maluku Sea, the Seram Sea and nearby the Arafuru Sea current velocity reaches 40cm / s.